Variation in the production of plant tissues bearing extrafloral nectaries explains temporal patterns of ant attendance in Amazonian understorey plants. (29th January 2020) - Nogueira, Anselmo; Baccaro, Fabricio B.; Leal, Laura C.; Rey, Pedro J.; Lohmann, Lúcia G.; Bronstein, Judith L.
Abstract: Information on direct and indirect drivers of temporal variation in ant–plant interactions is scarce, compromising our ability to predict the functioning of these ecologically important interactions. We investigated the roles of precipitation, ant activity, abundance of young plant tissues bearing extrafloral nectaries (EFNs) and EFN phenotypes in the establishment of EFN‐mediated ant–plant interactions throughout the year in Amazonia, Brazil. We hypothesized that the frequency of ant–plant interactions follows a predictable seasonal pattern, being higher in wetter periods, during which plants invest more in the production of new plant tissues bearing EFNs, ultimately promoting ant attendance. We surveyed and tagged every understorey Bignonieae plant rooted inside 28, 500‐m 2 plots, and recorded ant–EFN interactions on each plant five times throughout the year. We also sampled ants with honey baits to estimate temporal variation in general ant activity. Contrary to our hypothesis, the proportion of plants tended by ants in each plot was higher in drier, not wetter, months. Ant attendance was indirectly and negatively related to precipitation, which was attributed to a decrease in the proportion of plants producing new EFN‐bearing plant tissues during the wetter period. Additionally, seasonal variation in an ant activity did not explain temporal patterns of plant attendance. At the plant level, ant attendance increased strongly with the number of recently formed shoot nodes, and ants almost never attended plants with limited or no young tissue. Among the 12 most abundant Bignonieae species, the amount of young tissue was the most important predictor of ant attendance, secondarily explained by the EFN secretory area. Synthesis . Our results suggest that seasonal variation in the production of new plant tissues bearing EFNs is the primary driver of the temporal patterns of EFN–plant attendance by ants in this system. Contrary to our expectations, production of new plant tissue is higher in the drier months of the year, which in turn boosts the frequency of interactions between ants and EFN‐bearing plants in the dry season. These results highlight the role of plant phenology in the remarkable variation encountered in ant visitation to EFN‐bearing plants in both space and time. Abstract : Our results suggest that seasonal variation in the production of new plant tissues bearing extrafloral nectaries (EFNs) is the primary driver of the temporal patterns of EFN–plant attendance by ants in this system. Contrary to our expectations, production of new plant tissue is higher in the drier months of the year, which in turn boosts the frequency of interactions between ants and EFN‐bearing plants in the dry season. These results highlight the role of plant phenology in the remarkable variation encountered in ant visitation to EFN‐bearing plants in both space and time.